Disturbances of Modulating Molecules (FOXP3, CTLA-4/CD28/B7, and CD40/CD40L) mRNA Expressions in the Orbital Tissue from Patients with Severe Graves' Ophthalmopathy. (12th January 2015) - Pawlowski, Przemyslaw; Wawrusiewicz-Kurylonek, Natalia; Eckstein, Anja; Reszec, Joanna; Luczynski, Wlodzimierz; Johnson, Kristian; Kretowski, Adam; Bakunowicz-Lazarczyk, Alina; Gorska, Maria; Szamatowicz, Jacek; Chyczewski, Lech; Mysliwiec, Janusz
Abstract : Purpose. To evaluate the relationship between the expression of orbital tissue mRNA for FOXP3, CTLA-4/CD28/CD80/CD86, and CD40/CD40 and the severity of Graves' orbitopathy (GO). Material and Methods. Orbital tissue was obtained from 26 patients with GO, with mild (n = 6 ) or severe GO (n = 20 ), and 7 healthy controls. The expression of mRNA of FOXP3, CTLA-4/CD28/CD80/CD86, CD40/CD40L was measured by RT-PCR. TCR and CD3 were evaluated by immunohistochemistry. Results . Higher mRNA for FoxP3 (relative expression: 1.4) and CD40 (1.27) and lower expression of CTLA-4 (0.61) were found in the GO tissues versus controls. In severe GO as compared to mild GO higher mRNA expression for FoxP3 (1.35) and CD40 (1.4) and lower expression for CTLA-4 (0.78), CD28 (0.62), and CD40L (0.56) were found. A positive correlation was found between FOXP3 mRNA and CD3 infiltration (R = 0.796, P = 0.0000001 ). Conclusions . The enhanced FOXP3 mRNA expression in GO samples may suggest the dysfunction of FOXP3 cells in the severe GO. The diminished mRNA expression of CTLA-4 in severe GO may indicate inadequate T regulatory function. The enhanced mRNA expression of CD40 in severe GO and negative correlation to CRP mRNA may suggest their role in the active and inactive GO.